Production and Utilization of Crop Residues in Three Agro Ecological Zones of Eastern Shoa Zone, Ethiopia - Tesfaye Alemu; Pornsri Chairatanayuth; Pravee Vijchulata; SayanTudsri (Agriculture and Natural Resources, 2006)
To assess the production and utilization of crop residues in East Shoa Zone of Oromiya Regional State, Ethiopia, 3 Agro Ecological Zones (AEZs), namely, sub-moist (SM2), sub-humid (SH2) and semiarid (SA2) were chosen based on their large area coverage and, a total of 300 households were proportionally selected from these AEZs and interviewed using structured questionnaire. Even if the total annual crop residue produced per household was not statistically different, the contribution of each type of crop residue to the total annual crop residue production per household varied (p<0.05) among the AEZs. With regard to utilization, farmers in all the three AEZs used almost all types of their crop residues primarily for animal feeding. Alternative uses of crop residues were observed to vary more with the type of residue than with the AEZs. It could be concluded that with an annual average production of 0.67 to 1.01 tons per TLU of a household, crop residues contributed to 26 to 40% of the total annual maintenance feed requirement of ruminants. Through the use of improved see ds and other inputs that boosted both grain and residue yields, and by the application of better ways of collection and storage that minimized wastages, farmers could derive more benefits from these valuable feed resources.